Tourism Demand Modelling and Forecasting: An Overview - Ramos, Célia M.Q.; Rodrigues, Paulo M.M. (Revista de Turismo Contemporâneo, 2014)
The research of tourism demand of a country or region is indispensable since the tourist demand and economic growth are positively related. In the analysis of tourism demand, which should be initiated by the identification of factors and determinants which explain the preference for a particular destination, it is necessary to identify the most appropriate functional relationship between the independent variables in order to define the model, more representative, for the purpose of the study, which investigates about what influences or motivates the search for a specific tourist destination while allows the forecasting of their development. Thus, this article aims to contribute to a better understanding of the problems associated with the process of tourism demand modelling and forecasting for a given destination.